Peraturan Daerah Nomor 16 Tahun 2014 tentang Penataan dan Pemberdayaan Pedagang Kaki Lima pada Penegakan Hukum dan Sanksi serta Kendala di Kabupaten Grobogan - Wibowo, Fajar Satrio; Listiyarini, Dyah; Megawati, Wenny (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study discusses the Implementation of Local Regulation Number 16 of 2014 regarding the Regulation and Empowerment of Street Vendors in Grobogan Regency. It is triggered by the rapid economic development in the region, which has resulted in a significant increase in the participation of street vendors in economic development efforts through street vending activities, which are increasingly popular among the people of Grobogan Regency. The study examines how the law enforcement is carried out on Local Regulation Number 16 of 2014 concerning the regulation and empowerment of street vendors in Grobogan Regency. Additionally, the research also highlights the sanctions imposed when street vendors violate these local regulations, and identifies the challenges faced by the Municipal Police officers in carrying out their duties to regulate street vendors. The research applies a normative juridical approach in its methodology with a descriptive analysis specification. Despite some challenges faced by the officers in the field, the law enforcement of Local Regulation Number 16 of 2014 regarding the Regulation and Empowerment of Street Vendors in Grobogan Regency continues to proceed in an orderly manner and can be overcome by field officers.